A STUDY ON QUALITY WORK LIFE OF EMPLOYEE - Challa, Raju.; REVATHI, N. (IJRDO - Journal of Business Management, 2018)
The main objective of this paper is to study the quality work life of employee, which is all-inclusive notion of life and living conditions. It is the quality of the content of relationship between employees and their total working environment, with human dimension. A process through which the stakeholders in the organization, management, unions and employees-learn how to work together better. Employees should be treated in a fair and supportive manner, to open up communication channel at all levels, to offer employees opportunities to participate in decisions affecting them, and to empower them to carry through assignments. Moreover, quality of work life through employee involvement consists of a variety of systematic methods that enable employees to participate in the decisions that affect them and their relationship with the organization. The paper suggests that strengthening the employees working environment work organization are able to satisfy important personal needs through their experience in the organization.